Digital food cultures - Lupton, Deborah; Feldman, Zeena (London: Routledge, 2020)
"This book explores the interrelations between food, technology and knowledge-sharing practices in producing digital food cultures. Digital Food Cultures adopts an innovative approach to examine representations and practices related to food across a variety of digital media: blogs and vlogs (video blogs), Facebook, Instagram, YouTube, technology developers' promotional media, online discussion forums, and self-tracking apps and devices. The book emphasises the diversity of food cultures available on the internet and other digital media, from those celebrating unrestrained indulgence in food to those advocating very specialised diets requiring intense commitment and focus. While most of the digital media and devices discussed in the book are available and used by people across the world, the authors offer valuable insights into how these global technologies are incorporated into everyday lives in very specific geographical contexts. This book offers a novel contribution to the rapidly emerging area of digital food studies and provides a framework for understanding contemporary practices related to food production and consumption internationally"--
Includes bibliographical references and index.
Keywords: Food habits -- Cross-cultural studies; Digital media -- Cross-cultural studies; Food consumption -- Cross-cultural studies